ANALISIS PENATAUSAHAAN ASET TETAP DAERAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN TELUK BINTUNI - Werbette, Ira Selviana Biloro; Salle, Agustinus; Allo Layuk, Paulus K. (Universitas Cenderawasih, 2025)
This research aims to analyze the optimization of regional asset administration conducted by the Regional Financial and Asset Management Agency (BPKAD) of Teluk Bintuni Regency. The primary focus includes the asset administration process, the constraints encountered during implementation, and optimization strategies to improve effectiveness and efficiency. The study employs a qualitative-descriptive method with an exploratory approach. Data were collected through in-depth interviews with relevant officials and documentation studies of the Audit Board of Indonesia (BPK) reports, regional financial statements, and applicable regulations. Thematic analysis was utilized to identify key patterns and themes related to regional asset management. The results indicate that while asset administration in Teluk Bintuni Regency refers to Government Regulation (PP) No. 27 of 2014 and utilizes the Regional Management Information System for Regional Property (SIMDA BMD), several significant obstacles remain. These include low discipline among asset users, disorganized recording practices, weak coordination between Regional Government Agencies (OPD), and limited human resource competency in asset administration. To optimize management, this study recommends several strategies: increasing compliance through socialization and the enforcement of sanctions, improving technology-based recording systems for better accuracy and transparency, and strengthening inter-agency coordination through stricter reporting mechanisms. Furthermore, enhancing human resource capacity through training and certification is crucial to ensuring effective regional asset management.